Perancangan Kreatif Kolaboratif Arsitektur Gapura Berkarakter Lokal Wisata Bumi Perkemahan Bedengan desa Wisata Selorejo - Ponimin, Ponimin; Wardana, Mitra Istiar; Raharjo, Timbul; Rakuti, Nurhadi (Universitas Negeri Malang, 2021)
Designing iconic gate architecture for Bumi Perkemahan Bedengan of Selorejo Village tourism area with local character plays important role for tourism area development. The design meant not only for beauty aspect, but also build local-based artistic visual image as tourists attraction. It can be reached by collaborative creative method. Done by cooperation of local tourism area administrator team with LP2M UM as implementer. This collaborative work started from user partner needs analysis. The analysis result used as reference to formulate design concept for gate architecture, realized gate design concept, analysing the result, evaluating and improving collaborative work result. The activity result comes in design and gate product set built on tourism area to strengthen tourism area image through gate design icon with local character from environment and local culture as creation idea.